On the path to sustainability: Key issues on Nigeria's sustainable energy development - Norbert Edomah (Energy Reports, 2016)
In the face of scarcity of energy resources and rising energy prices due primarily to a world of increasing demand, energy security concerns becomes more crucial both for private and public sector alike. At the same time, energy policies have been shifting and policy changes have become hard to predict because of radical changes in energy supply. This paper analyzes the barriers to sustainable energy development in Nigeria which are: (1) cost and pricing barriers, (2) legal and regulatory barriers, (3) market performance barriers. It concludes by highlighting some key policies that can help address some of the identified barriers in order to ensure a secured sustainable energy future for Nigeria.
Keywords: 330; Energy barriers; Energy policy; Energy security; Nigeria; Sustainable energy